A Real Time Home Automachine System Using Advanced Wireless Network Techniques - et. al., Gade Nagi Reddy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research work an advanced home auto machine technique are proposed with wireless network applications. In home applications many devices consume electrical energy heavily, due to this maintenance getting complex. Therefore, energy management and testing of appliances miniaturization is compulsory. In this study wireless communication-based GUI is implemented for hybrid home auto-machine. The Wi-Fi, Bluetooth and other gateway devices are continuously monitoring with runway scheduling algorithm. This technique is continuously monitoring the home appliances and balancing the energy management. The proposed algorithm providing high accuracy compared to existed methods.